HUBUNGAN PENGETAHUAN DAN SIKAP IBU TENTANG IMUNISASI BCG DENGAN PEMBERIAN IMUNISASI BCG PADA BAYI USIA 0-2 BULAN DI PUSKESMAS PAUH PADANG - Farida Ariyani (STIKes MERCUBAKTIJAYA, 2019)
CORELATION OF MOTHER’S KNOWLEDGE AND ATTITUDE ABOUT BCG TO IMMUNIZATION IN PRIMARY HEALTH CARE OF PAUH PADANG Farida Ariyani* Prodi D III Kebidanan STIKes MERCUBAKTIJAYA Padang Email: dzakwan.sayang@gmail.com/081374144408 ABSTRAK Introduction : Tuberculosis is a contagious disease that attacks the body organs especially the lungs. This disease is caused by Mycobacterium tuberculosis. The disease can be prevented by giving BCG immunization. Achievement of BCG immunization in Puskesmas Pauh in 2015 amounted to 91.8%. This figure is still below the target of achieving imunsasi BCG city of Padang namely 95%. The purpose of this study to determine the correlation between knowledge and attitudes of mothers about BCG immunization with BCG immunization in infants aged 0-2 months in Padang Pauh Health Center in 2016. Objective : The population of 1264 respondents. Sampling by accidental sampling with 93 respondents. Methode : The study was analytic with cross sectional design. The data collection is done in Puskesmas Padang Pauh, 2016. Data is collected directly by using a questionnaire. Processing of data starts from editing, coding, data entry, tabulating and dry. The data were analyzed by univariate and bivariate statistical test Chi-Square. Result : The results of the 93 respondents, 54 (58.1%) had a low level of knowledge, 34 people (36.6%) of them had given BCG immunization to the baby. And of the 39 (41.9%) who have a negative attitude 26 people (28%) did not immunize her baby. Bivariate analysis showed no association with the level of knowledge of immunization in infants aged 0-2 months and the relationship between mother attitude with BCG immunization in infants aged 0-2 months. Conclutionts : It can be concluded that the immunization tends to be given by mothers who have a positive attitude towards the BCG immunization, health workers are expected to be able to change the negative attitude into a positive attitude so that immunization of BCG can be accomplished with a maximum. Key word : BCG immunization, Knowledge, attitude